Hydroxyurea effectiveness in children and adolescents with sickle cell anemia: A large retrospective, population‐based cohort. Issue 1 (18th November 2016) - Quarmyne, Maa‐Ohui; Dong, Wei; Theodore, Rodney; Anand, Sonia; Barry, Vaughn; Adisa, Olufolake; Buchanan, Iris D.; Bost, James; Brown, Robert C.; Joiner, Clinton H.; Lane, Peter A.
Abstract : The clinical efficacy of hydroxyurea in patients with sickle cell anemia (SCA) has been well established. However, data about its clinical effectiveness in practice is limited. We evaluated the clinical effectiveness of hydroxyurea in a large pediatric population using a retrospective cohort, pre‐post treatment study design to control for disease severity selection bias. The cohort included children with SCA (SS, Sβ 0 thalassemia) who received care at Children's Healthcare of Atlanta (CHOA) and who initiated hydroxyurea in 2009‐2011. Children on chronic transfusions, or children with inadequate follow up data and/or children who had taken hydroxyurea in the 3 years prior were excluded. For each patient healthcare utilization, laboratory values, and clinical outcomes for the 2‐year period prior to hydroxyurea initiation were compared to those 2 years after initiation. Of 211 children with SCA who initiated hydroxyurea in 2009–2011, 134 met eligibility criteria. After initiation of hydroxyurea, rates of hospitalizations, pain encounters, and emergency department visits were reduced by 47% (<0.0001), 36% (P = 0.0001) and 43% ( P < 0.0001), respectively. Average hemoglobin levels increased by 0.7 g/dl ( P < 0.0001). Hydroxyurea effectiveness was similar across gender, insurance types and age, although there was a slightly greater reduction in hospitalizations in younger children. Am. J. Hematol. 92:77–81, 2017. © 2016 Wiley Periodicals, Inc.